Aging in Myanmar - KNODEL, John (Institutional Knowledge at Singapore Management University, 2017)
This spotlight provides an overview of thesituation of older persons in Myanmar, an under-studied country ofover-50-million population. Myanmar is of particular interest to researchersand policy makers, given its overall level of poverty and modestly rapidpopulation aging. Research on older persons, while increasing in recent years,remains sparse. Empirical evidence indicates that Myanmar older persons are inrelatively poorer health compared to those in neighboring countries. Many livein abject poverty and depend on their families for material support.Coresidence is very common and facilitates reciprocal exchanges acrossgenerations. Looking ahead, Myanmar confronts important challenges includingdemographic shifts that reduce availability of family support for older personsand increasing burden from chronic illnesses. Currently, government measuresare essentially absent, although a law on aging was drafted and is in theprocess to become legislation.